2015
DOI: 10.1371/journal.pone.0133054
|View full text |Cite
|
Sign up to set email alerts
|

Association Analysis of Simple Sequence Repeat (SSR) Markers with Agronomic Traits in Tall Fescue (Festuca arundinacea Schreb.)

Abstract: Tall fescue is widely used in temperate regions throughout the world as a dominant forage grass as well as a turfgrass, in pastoral and turf industry. However, the utilization of tall fescue was limited because of its leaf roughness, poor regeneration ability and poor stress resistance. New cultivars were desirable in modern pastoral industries exceed the potential of existing cultivars. Therefore, well understanding the agronomic traits and describing germplasms would help to overcome these constraints, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 56 publications
7
14
0
Order By: Relevance
“…This low R 2 value for each trait may be attributed to the role of many minor genes controlling the trait, outcrossing nature of smooth bromegrass, markers exhibiting minor quantitative effect, rare alleles, and complex allelic interactions [47,48]. These results are in agreement with the findings of Lou et al [32] and Sun et al [33] in tall fescue.…”
Section: Discussionsupporting
confidence: 90%
“…This low R 2 value for each trait may be attributed to the role of many minor genes controlling the trait, outcrossing nature of smooth bromegrass, markers exhibiting minor quantitative effect, rare alleles, and complex allelic interactions [47,48]. These results are in agreement with the findings of Lou et al [32] and Sun et al [33] in tall fescue.…”
Section: Discussionsupporting
confidence: 90%
“…Lou et al . [ 120 ] used 90 SSRs for the mapping QTLs for agronomic traits in Fescue. Gyawali et al .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, in the plant breeding programs and genotype conservation the population structure and genetic diversity information are valuable keys. Agromorphological traits are prerequisite to classify and describe genotype diversity (LOU et al, 2015). In the current study, all agro-morphological traits showed a signi cant difference between the ecotypes (except the number of branches).…”
Section: Discussionmentioning
confidence: 99%